Truth and metaphor and their implications - Abdul Hamid, Nur Aina Adlina; Aznan, Anees Mysarah; Mohd Salehuddin, Mardiyyah Mutmainnah; Bakri, Husna Najihah; Hanapi, Nureen Hafiza; Amram, Adriana Izzah (2024)
Slide Presentation: “Truth and metaphor and their implications”